The Pre-clinical Toolbox of Pharmacokinetics and Pharmacodynamics: in vitro and ex vivo Models - Herrera, Carolina (Frontiers in Pharmacology, 2019)
Prevention strategies against sexual transmission of human immunodeficiency virus (HIV) are essential to curb the rate of new infections. In the absence of a correlate of protection against HIV infection, pre-clinical evaluation is fundamental to facilitate and accelerate prioritization of prevention candidates and their formulations in a rapidly evolving clinical landscape. Characterization of pharmacokinetic (PK) and pharmacodynamic (PD) properties for candidate inhibitors is the main objective of pre-clinical evaluation. in vitro and ex vivo systems for pharmacological assessment allow experimental flexibility and adaptability at a relatively low cost without raising as significant ethical concerns as in vivo models. Applications and limitations of pre-clinical PK/PD models and future alternatives are reviewed in the context of HIV prevention.